Decision Support System for Determination of Salaries Employees in Civil Service Police Unit Deli Serdang With Simple Additive weighting method (SAW) - Yolanda, Mifta Reza; Simanjorang, R. Mahdalena (Information Technology and Science (ITScience), 2020)
This study examines how to design an application for the Deli Serdang Civil Service Police Unit in order to Facilitate the Process of Determining Salaries employee. With this application, it is hoped that it will make it Easier for the Office to Determine the determination of employee Salaries so that it is faster and more accurate. The SAW method certainly uses a more Appropriate assessment Because it is based on a criterion value of a predetermined preference weight. With the existence of accurate the data will be Able to minimize the time wasted and Be Able to use the system that is being designed. Data managed in the Office still uses Excel so that in its implementation the the data is still vulnerable to being scattered and the possibility of vulnerability to damage and loss of data.